Breastfeeding and Breast Milk – From Biochemistry to Impact, (Ed, Family Larson- Rosenquist Foundation) Georg Thieme Verlag KG 2018
DOI: 10.21428/3d48c34a.1154fbeb
|View full text |Cite
|
Sign up to set email alerts
|

5 Why Breastfeeding?

Abstract: The importance of optimum nutrition in the first months after birth • The effect of early nutrition on later life • The importance of good health and nutrition for mothers during pregnancy and throughout lactation 5.1 ▶ Fig. 5.4 Lower risk of overweight and obesity at early school age among more than 9,000 children in Bavaria, Germany (adjusted for confounding variables) in children ever breastfed versus never breastfed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) recommend exclusive breast-feeding (EBF) for the first 6 months of life, followed by the introduction of complementary foods (CF) along with continued breast-feeding up to the age of 2 years and beyond (5). Scientific studies and systematic reviews showed several short-and long-term benefits associated with breast-feeding, such as lower risk of death among breastfed children, protection against diarrhea, otitis media and respiratory infections, and lower odds of overweight and obesity, type-2 diabetes, and high systolic blood pressure later in life (6)(7)(8)(9)(10). Thus, promoting, protecting and supporting breastfeeding is an important public health priority.…”
Section: What Is Newmentioning
confidence: 99%
“…The World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) recommend exclusive breast-feeding (EBF) for the first 6 months of life, followed by the introduction of complementary foods (CF) along with continued breast-feeding up to the age of 2 years and beyond (5). Scientific studies and systematic reviews showed several short-and long-term benefits associated with breast-feeding, such as lower risk of death among breastfed children, protection against diarrhea, otitis media and respiratory infections, and lower odds of overweight and obesity, type-2 diabetes, and high systolic blood pressure later in life (6)(7)(8)(9)(10). Thus, promoting, protecting and supporting breastfeeding is an important public health priority.…”
Section: What Is Newmentioning
confidence: 99%
“…The nutritional and functional properties of infant formula should ensure healthy growth and development, serving a similar function and providing similar benefits as HM as much as possible. HM composition is believed to be selected by evolution to provide the nutrients and energy to support adequate growth and development of human infants ( 32 ), and thus provides some guidance as to infant FA intakes that are likely adequate, even though the HM lipid composition varies markedly. It is also important to consider that an identical intake level of a substrate in infant formula as observed in HM does not by itself ensure safety and suitability.…”
Section: Hm Composition May Provide Guidance On Adequate Infant Fa Intakesmentioning
confidence: 99%
“…It has been postulated that some of these changes may match changing nutritional requirements of the growing/developing infant. For example, the observed increase in fat content with a concomitant decrease of protein-to-fat and protein-to-energy ratios during the transition from colostrum to mature milk is likely to reflect the decreasing weight gain velocity with an increasing postnatal age ( 32 ). The determinants and biological relevance of changes in the FA composition of HM during the transition to mature milk, in particular the decline in HM ARA and DHA with an increasing duration of lactation, is less clear ( 2 ), and is considered to likely reflect the depletion of maternal body stores of LCPUFA rather than declining needs of the infant.…”
Section: Hm Composition May Provide Guidance On Adequate Infant Fa Intakesmentioning
confidence: 99%
“…Infant protein requirements are related to weight gain velocity which rapidly declines during the first months of life. Accordingly, protein requirements per kg bodyweight at 6 months of age are only 2/3 of those after birth, and protein supply per kg bodyweight in an exclusively breastfed infant at 6 months is only 55% of that after birth [19]. The use of adequately composed follow-up formula can help to better match dietary intake to changing needs with age.…”
Section: Follow-up Formulaementioning
confidence: 99%